David Hunter Hubel, the ‘Circe effect’, and SARS-CoV-2 infection of the human visual system - Walter J. Lukiw (Frontiers in Bioscience-Landmark, 2022)
David Hunter Hubel (1926–2013) was an internationally recognized neurophysiologist and vision neuroscientist noted for his life-long studies on the columnar structure and highly integrated function of the brain’s primary and secondary visual cortex. He was co-recipient with the American neuropsychologist and neurobiologist Roger Wolcott Sperry (1913–1994) and the Swedish neurophysiologist Torsten Nils Wiesel (1924-present) of the 1981 Nobel Prize in Physiology or Medicine, for their significant discoveries concerning the functional specialization of the cerebral hemispheres, the layered structure of the human cerebral visual cortex and information processing in the visual system, how the human visual cortex is organized into columns, and how this remarkable cellular organization and connectivity for the human visual system can be modified by lifestyle, experience, aging and disease. This commentary integrates these significant findings with current observations on SARS-CoV-2, the causative agent of COVID-19, and its invasion of the human visual system via the angiotensin converting enzyme 2 (ACE2) receptor.